The cost-effectiveness of introducing a vaccine for the prevention of herpes zoster and post-herpetic neuralgia in elderly Danes - Lone Bilde; Thomas T Nielsen; Finn Ronholt; Marie Kruse (University of Oslo, 2016)
Herpes Zoster is an unpleasant and painful skin condition associated with a risk of developing post-herpetic neuralgia if the pain persists. Herpes Zoster most often occurs in elderly people. This study examines the cost-effectiveness of introducing a vaccine against Herpes Zoster in the Danish health care sector. The cost-effectiveness is examined in a Markov lifetime model framework and populated with Danish data and results from the international literature. From the base case analysis, with an ICER of DKK 261,372 per QALY gained, it seems that an implementation of a vaccine against HZ in the Danish population aged 65 years or more might be cost-effective within generally accepted incremental cost-effectiveness thresholds. Furthermore, an age-specific analysis showed that although the incidence of herpes zoster generally increases with age, targeting the vaccine at persons aged 50-69 years rather than the persons aged 65 years or more, seems to be a more cost-effective strategy from the societal perspective. However, these results are very sensitive to changes in vaccine price, utility values, discount rates, and especially, to the vaccine duration of protection. Published: Online December 2016. In print December 2017.